On the problem of error propagation in classier chains for multi-label classification. Data Analysis, Machine Learning and Knowledge Discovery - Senge, Robin; del Coz, J.J.; Hüllermeier, Eyke (In Proceedings of GFKL-2012, 36th Annual Conference of the German Classification Society, Studies in Classification, Data Analysis and Knowledge Organization, Hildesheim, Germany)

Local clique merging: An extension of the maximum common subgraph measure with applications in structural bioinformatics, Algorithms from and for Nature and Life - Fober, T.; Klebe, G.; Hüllermeier, Eyke (In Proceedings GFKL-2011, Conference of the German Classification Society, Frankfurt Germany)

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013,)

DAG - Index - A Compressed Index for XML Keyword Search - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies)

Ordinal Choquistic regression - Fallah Tehrani, A.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2013 8th International Conference on the European Society for Fuzzy Logic and Technology, Milano, Italy)

Fuzzy Pattern Trees as an alternative to rule-based fuzzy systems: Knowledge-driven, data-driven and hybrid modeling of colour yield in poyester dyeing, Edmonton, Canada - Nasiri, N.; Fober, T.; Senge, Robin; Hüllermeier, Eyke (in Proceedings IFSA-2013 World Congress of the International Fuzzy Systems Association, Edmonton, Canada)

Implementing Efficient Updates in Compressed Big Text Databases - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita; Schlüßler, Jonathan (International Conference on Database and Expert Systems Applications)

How visualization courses have changed over the past 10 years - Owen, G Scott; Domik, Gitta; Ebert, David S; Kohlhammer, J{\; Rushmeier, Holly; Santos, Beatriz Sousa; Weiskopf, Daniel (IEEE computer graphics and applications)

Animatronics Workshop: A Theater+ Engineering Collaboration at a High School - Alford, Jennifer Ginger; Jacob, Lucas; Dietz, Paul (IEEE computer graphics and applications)

Visualizing Dissections of the Heart in a Dataflow-based Shader Framework for Volume Rendering - Arens, Stephan; Bolte, Matthias; Domik, Gitta (Vision, Modeling & Visualization)

Multilabel classification for exploiting cross-resistance information in HIV-1 drug resistence prediction - Heider, D.; Senge, Robin; Cheng, W.; Hüllermeier, Eyke (Bioinformatics)

Chest pain in primary care: is the localization of pain diagnostically helpful in the critical evaluation of patients? A cross sectional study. - Bösner, S.; Bönisch, K.; Haasenritter , J.; Schlegel, P.; Hüllermeier, Eyke; Donner-Banzhoff, N. (BMC Family Practice)

Diagnose im Kontext - eine erweiterte Perspektive - Haasenritter, J.; Viniol, A.; Becker, A.; Bösner, S.; Hüllermeier, Eyke; Senge, Robin; Donner-Banzhoff, N. (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen (ZEFQ))

Evolving fuzzy pattern trees for binary classification on data streams - Shaker, A.; Senge, R.; Hüllermeier, Eyke (Information Sciences)

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Multi Reflection of Lamb Wave Emission in an Acoustic Waveguide Sensor - Schmitt, Martin; Olfert, Sergei; Rautenberg, Jens; Lindner, Gerhard; Henning, Bernd; Reindl, Leonhard (Sensors)

Detection of coatings within liquid-filled tubes and containers by mode conversion of leaky Lamb waves - Schmitt, M.; Schmidt, K.; Olfert, S.; Rautenberg, J.; Lindner, G.; Henning, Bernd; Reindl, L. M. (Journal of Sensors and Sensor Systems)
Abstract. In this paper, a new acoustic sensor principle for coating detection within liquid-filled tubes and containers based on mode conversion of leaky Lamb waves is introduced. Leaky Lamb waves are excited and detected by single-phase transducers, which are attached on the outer side of a tube or container. By transmission time and amplitude measurements, coating formation within the liquid-filled tube and container is detected non-invasively. This new sensor principle is subdivided into the separate considerations of Lamb wave excitation, mode conversion and inverse mode conversion. The Lamb wave excitation by a single-phase transducer is visualized by scanning laser Doppler vibrometer imaging. The mode conversion process of leaky Lamb waves is measured by membrane hydrophone measurements and Schlieren visualization; afterwards, the measured emission angles are compared with the theoretical one. The inverse mode conversion process of pressure waves back to leaky Lamb waves is visualized by Schlieren images. By merging the results of Lamb wave excitation, mode conversion and inverse mode conversion, the new sensor concept is explained. Theoretical considerations and measurement results of adhesive tape coating inside a liquid-filled plastic tube and a liquid-filled stainless steel container verify the new acoustic sensor principle. Finally the measuring sensitivity and the technical realization are discussed.

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd (tm - Technisches Messen)

B5.4 - Signal Processing for Single Transducer Distance Measurement Applications to Reduce the Blind Zone - Schröder, A.; Henning, Bernd

Utilizing ultrasound material parameter determination for the characterization of different stages of ageing in Polyamide 6 - Bause, Fabian; Budde, Christopher; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar
The condensation polymer Polyamide 6 (PA 6) is a thermoplastic resin with high tensile strength and rigidity at comparatively low costs for raw material and processing. This is why PA 6 is a common material for the production of ropes, gears or bearings. Apart from that, a relative new application is the thermoforming of glass fibre laminate sheets with PA 6 as matrix material. The prediction the rest of life period of such high-tech materials is still a research objective. A first step, and also part of this contribution, is the nondestructive investigation of the matrix material. The ageing of PA 6 is mainly affected by thermo- and photo-oxidation as well as post-condensation, which e.g. results in a change of physical properties. For this contribution the acoustical and mechanical material parameters of artificially aged PA 6 have been determined with high frequency ultrasound (1 MHz) and quasi-static experiments. We will give a short description of both experimental setups as well as the ageing procedure. Finally we will discuss the correlation between the experimental results, finding that there is a good correlation between sound velocity and tensile strength.

Ultrasonic Waveguide Signal Decomposition Using the Synchrosqueezed Wavelet Transform for Modal Group Delay Computation - Bause, Fabian; Huang, Boqiang; Kunoth, Angela; Henning, Bernd
Due to the modal behavior of geometrically bounded media, ultrasonic guided waves propagate in waveguides as a combination of multiple dispersive wave packets, which can be simulated as a PDE-problem. Given an excitation in time and space, multiple eigen-modes derived from solving the PDE may propagate each with different dispersion characteristics and weight. Considering a broad-band pulse exciting from one side of a hollow cylindrical waveguide, the received signal at the other side consists of all propagating eigen-modes that can be considered approximately as the narrow band signals. The synchrosqueezed wavelet transform (SWT) is employed to sharpen the time-frequency representation (TFR) of the received waveguide signal. Using a ridge detection algorithm, we successively separate the synchrosqueezed TFR into several narrow band TFRs which can be identified as oscillatory components with time-varying frequency. Then those separated TFRs are reconstructed as narrow band signals using the inverse SWT. Based on an analytical model of the waveguide, we observe that the decomposed signals are similar to those dominant eigen-modes simulated above. Moreover, also the group delay and, therefore, the group velocity of each decomposed signal can be estimated well. This is of high interest when analyzing the characteristic of a given waveguide, such as acoustical property measurements or non-destructive testing.

Utilizing interval-Newton approach for the reliable computation of roots in analytical waveguide modeling - Bause, Fabian; Unverzagt, Carsten; Walther, Andrea; Henning, Bernd

Reliable Computation of Roots in Analytical Waveguide Modeling Using an Interval-Newton Approach and Algorithmic Differentiation - Bause, Fabian; Walther, Andrea; Rautenberg, Jens; Henning, Bernd (Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Modellgestützte NIR-Materialfeuchtemessung mittels Multidetektoranordnung - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd (Technisches Messen)
Zur berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung genutzt. Diese nichtinvasive und schnelle Methode ist geeignet sowohl zur Bestimmung der Feuchte von Schüttgütern als auch zur Charakterisierung von Trocknungsprozessen von Lacken. Die reflektierte Strahlung ist dabei abhängig von Absorption und Streuung in der Beschichtung sowie von den temporären und lokalen Reflexionseigenschaften des Messobjektes. ln dieser Untersuchung ist ein experimenteller Aufbau zur simultanen Messung der gerichteten und der diffus reflektierten Strahlungsanteile realisiert.

Untersuchung zum Trocknungsverhalten poröser Materialien durch NIR-Reflexionsmessungen - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd

A modified electrode topology with increased sensitivity of electrical impedance to piezoelectic material parameters - Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Improved Signal Processing for an Ultrasonic Distance Sensor with Reduced Blind Zone - Schröder, Andreas; Henning, Bernd (Proceedings of the International Conference on Acoustics)
Single transducer distance sensors have a blind zone because normally the electrical received signal cannot be detected during transmitting. There are several approaches to realize a simultaneous transmit and receive operation. Digital signal processing is the best solution for narrow band systems (air ultrasound transducer) especially when the transmitted signal is coded. Thereby a mathematical model is used to estimate the electrical received signal. A drawback of the digital signal processing is the required computing time to estimate the model and the time of flight of an echo. In this contribution the computing time is reduced significantly by using base band signals for the signal processing. The signal-processing is subdivided into the following steps: Preprocessing, model identification, estimation of the received signal and echo detection. Beside the model identification the signal-preprocessing is an important part of the system. It depends on the time of flight of an echo (close echo, far echo) and the state of the system (single measurement, averaging). The whole system is evaluated with measurements using a 40 kHz air ultrasound transducer in front of a reflector with varying distances between 0 mm and 1000 mm.

Modified electrode shape for the improved determination of piezoelectric material parameters - Unverzagt, Carsten; Rautenberg, Jens; Henning, Bernd; Kulshreshtha, Kshitij (Proceedings of the 2013 International Congress on Ultrasonics)

A Comparison of Alternative Ways to Identify Singular Matrices - Walther, Andrea; Bause, Fabian; Henning, Bernd

Adaptive Test and Diagnosis of Intermittent Faults - Cook, Alejandro; Rodriguez Gomez, Laura; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Learning to rank lexical substitutions - Szarvas, G.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings EMNLP-2013 Conference on Empirical Methods in Natural Language Processing, Seattle, USA)

Optimizing the F-measure in multi-label classification: Plug-in rule approach versus structured loss minimization - Dembczynski, K.; Jachnik, A.; Kotlowski, W.; Waegeman, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Top-k selection based on adaptive sampling of noisy preferences - Busa-Fekete, Robert; Szoreny, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Preference-based CBR: General ideas and basic principles - Hüllermeier, Eyke; Cheng, W. (in Proceedings IJCAI-13, 23rd international Joint Conference on Artificial Intelligence, Beijing, China)

Rule chains for visualizing evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

Recovery analysis for adaptive learning from non-stationary data streams - Shaker, Ammar; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

On Semeai Detection in Monte-Carlo Go. - Graf, Tobias; Schäfers, Lars; Platzner, Marco (Proceedings of the International Conference on Computers and Games (CG))

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Laemmle, Benjamin; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Weigel, Robert; Koelpin, Alexander; Kissinger, Dietmar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz f T SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm 2 . The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P 1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P 1dB of -17 dBm.

Integrator and digitizer for a non-coherent IR-UWB receiver - Digel, Johannes; Masini, Michelangelo; Grözing, Markus; Berroth, Manfred; Fischer, Gunter; Olonbayar, Sonom; Gustat, Hans; Scheytt, Christoph (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Impulse-radio ultra-wideband systems (IR-UWB) provide short-range wireless communication and precise localization simultaneously. Especially non-coherent IR-UWB reduces the system complexity which enables the design of low-power receivers. This paper presents an integrating digitizer which integrates rectified baseband pulses of an IR-UWB signal and provides the digitized data to the digital baseband of the receiver. The integrator is composed of two time-interleaved (TI) operational amplifiers with capacitive feedback. With this structure, the integrator can be periodically reset without introducing a dead time between two integration periods. The analog-to-digital conversion is performed by a 6 bit 62.4 MS/s successive approximation register analog-to-digital converter (SAR ADC). The integrating digitizer chip is realized in a 250 nm SiGe:C BiCMOS technology from IHP.

A low-cost miniature 120GHz SiP FMCW/CW radar sensor with software linearization - Sun, Yaoming; Marinkovic, Miroslav; Fischer, Gunter; Winkler, Wolfgang; Debski, Wojciech; Beer, Stefan; Zwick, Thomas; Girma, Mekdes Gebresilassie; Hasch, Jürgen; Scheytt, Christoph (Solid-State Circuits Conference Digest of Technical Papers (ISSCC), 2013 IEEE International)
This paper presents an integrated mixed-signal 120GHz FMCW/CW radar chipset in a 0.13μm SiGe BiCMOS technology. It features on-chip MMW built-in-self-test (BIST) circuits, a harmonic transceiver, software linearization (SWL) circuits and a digital interface. This chipset has been tested in a low-cost package, where the antennas are integrated. Above 100GHz, our transceiver has achieved state-ofthe-art integration level and receiver linearity, and DC power consumption.

Towards mm-wave System-On-Chip with integrated antennas for low-cost 122 and 245 GHz radar sensors - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Complex integrated 122 and 245 GHz SiGe BiCMOS transceiver ICs as well as an efficient broadband on-chip antenna are presented. The ICs target radar and sensing applications for the ISM bands at 122 and 245 GHz. Due to high level of integration and basic mm-wave self-testing production as well as test cost are dramatically reduced. Furthermore a compact and efficient on-chip antenna allows for chip-on-board mounting without RF interfaces.

49 GHz 6-bit programmable divider in SiGe BiCMOS - Ergintav, Arzu; Sun, Yaoming; Scheytt, Christoph; Gürbüz, Yasar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
In this paper, a 6-bit true modular programmable frequency divider with division ratios ranging from 64 to 127 is reported. It is composed of a divider chain of 6 divide-by-2/3 cells, and ECL stages that are introduced as synchronization circuits for programming inputs. The synchronization circuits have CMOS input for compatibility with programming circuits. The stand-alone divider chain is functional up to an input clock frequency of 49 GHz. The combination of the divider chain with synchronization circuits is functional up to 44 GHz. The 6 stage divider draws 34 mA current from a 2.7 V supply. The synchronization circuits draw 30 mA from a 3 V supply. The circuit is fabricated in a 0.13 μm SiGe BiCMOS technology, and is well suited for millimeter-wave phase-locked loop (PLL) circuits which require fine frequency resolution.

245 GHz subharmonic receivers in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium)
Two subharmonic receivers for 245 GHz spectroscopy sensor applications in the 245 GHz ISM band have been proposed. One receiver consists of an 2nd APDP (antiparallel diode pair) passive SHM (subharmonic mixer), a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA (power amplifier). The other consists of a single-ended four-stage CB (common base) LNA, an 2 nd APDP passive SHM, an IF amplifier, a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA. The receivers are fabricated in a SiGe:C BiCMOS technology with f T /f max =300/500 GHz. The measured conversion gain are -17 dB rsp. 10.6 dB at 245 GHz with 3-dB bandwidths of 13 GHz rsp. 14 GHz, and the single-side band noise figure are 17 dB rsp. 20 dB; the two receivers dissipates a power of 213 mW and 312 mW, respectively.

A 240 GHz Direct Conversion IQ Receiver in 0.13 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium,)
A 240 GHz direct conversion IQ receiver manufactured in 0.13 SiGe BiCMOS technology with f T /f max of 300/500 GHz is presented. The receiver consists of a four stage LNA, an active power divider, an LO IQ generation network, and direct down-conversion fundamental mixers. The integrated IQ receiver yields a conversion gain of 18 dB, an 18 dB simulated DSB NF, and a 3 dB bandwidth of 25 GHz. The required 245 GHz LO power is in the order of -10 dBm. The receiver exhibits an IQ amplitude and phase imbalance of 1 dB and 3° respectively. It draws 135 mA from the 3.5 V supply and 20 mA from 2 V.

245 GHz Subharmonic Receiver in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Meliani, Chafik (IEEE International Microwave Symposium, Advances in Low Noise Amplifiers and Receivers)
A subharmonic receiver for 245 GHz spectroscopy sensor applications have been proposed. The receiver consists of a CB (common base) LNA, 2 nd transconductance SHM (subharmonic mixer) and a 120 GHz push-push VCO with 1/64 divider. The receiver is fabricated in f T /f max =300/500 GHz SiGe: C BiCMOS technology. Its measured single-ended gain is 14.3 dB at 245 GHz with tuning range of 15 GHz, and the single-side band noise figure is 19 dB. The input 1-dB compression point is at -24 dBm. The receiver dissipates a power of 200 mW.